Гамільтонова геометрична зв'язність, асоційована з адіабатично збуреними гамільтоновими системами, та існування адіабатичних інваріантів - Прикарпатський, Я.А. (Український математичний журнал, 2008)
Изучаются дифференциально-геометрические свойства гамильтоновых связностей на симплектических многовидах для адиабатически возмущенной гамильтоновой системы. В частности, сконструирована ассоциированная гамильтоновая связность на главном расслоении и приведено ее описание в терминах ковариантных производных и формы кривизны соответствующей связности. Differential-geometric properties of the Hamiltonian connections on symplectic manifolds for the adiabatically perturbed Hamiltonian system are studied. Namely, the associated Hamiltonian connection on the main foliation is constructed and its description is given in terms of covariant derivatives and the curvature form of the corresponding connection.